Lung. (January 2016) - Valapour, M.; Skeans, M. A.; Smith, J. M.; Edwards, L. B.; Cherikh, W. S.; Callahan, E. R.; Israni, A. K.; Snyder, J. J.; Kasiske, B. L.
ABSTRACT: Lungs are allocated to adult and adolescent transplant candidates (aged ≥ 12 years) on the basis of age, geography, blood type compatibility, and the lung allocation score (LAS), which reflects risk of waitlist mortality and probability of posttransplant survival. In 2014, 2458 active candidates aged 12 years or older, the most of any year, were added to the list; 1949 transplants were performed. Overall median waiting time to transplant for candidates listed in 2014 was 3.7 months. Candidates undergoing lung transplant in 2014 were sicker than ever before with median LAS 44.4. Measures of short‐term survival continue to improve; however, long‐term survival has plateaued since the implementation of the LAS in 2005; at 5 years posttransplant, 42.4% of recipients had died. In 2014, 30 new active child (ages 0‐11) candidates were added to the list; 19 transplants were performed. Incidence of patient death was 7.1% at 6 months and 10.8% at 1 year for transplants in 2013, 29.7% at 3 years for transplants in 2009‐2010, and 42.7% at 5 years for transplants in 2007‐2008. By age, 5‐year patient survival was poorest for recipients aged younger than 1 year.